THE EFFECT OF EDTA BLOOD STORAGE TIME AND ROOM TEMPERATURE ON THE EXAMINATION OF ERYTHROCYTE SEDIMENTATION RATE - Nabila, Lazulpa; Durachim, Adang; Hayati, Eem; Noviar, Ganjar (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Erythrocyte Sedimentation Rate (ESR) is an examination that aims to determine the speed of erythrocytes settling in the blood measured for 1 hour. The examination of ESR performed within 2 hours at most. However, the examination is often not performed immediately due to several reasons that cause delays for several hours. The room temperature during the examination affects the examination. The temperature in West Java has the highest average reaching 32°C. Aims: To determine an effect of EDTA blood storage time and room temperature on the examination of ESR. Method: This research is included in the type of quasi eksperimental research by involving variations in blood storage time immediately, 4 hours, and 5 hours and room temperature during examination is room temperature 20-25oC and temperature 29-32oC. Result: The result of this study showed that there was a significant effect of the variable EDTA blood storage time and room temperature on the examination of ESR which is indicated by the value of Sig. 0,00 (Sig. 0,05). This is because EDTA blood stored more than 2 hours after blood collection will affect the shape of the cells and the temperature can affect the settling speed. Conclusion: Based on the results of statistical tests, it can be concluded that there is an effect of EDTA blood storage time and room temperature on the examination of ESR